Understanding women’s time use in farming communities: Insights from the Women’s Empowerment in Agriculture Index - Abdu, Aishat; Malapit, Hazel J.; Go, Ara (International Food Policy Research Institute, 2025)
Agricultural programs targeting women may increase women’s work burdens and shift the distribution of work between productive and reproductive tasks. Complementary information on women’s sense of control over their time highlights additional benefits of agricultural programs beyond changes in women’s workloads. Despite program interventions, gender norms often persist, affecting how communities perceive work intensity and division of responsibilities between men and women. The relationship between women’s time use and nutrition is complex and interacts with mediating factors, requiring a multifaceted approach to program design and evaluation. Evidence linking time use data to nonfarm work is lacking, highlighting the need to leverage WEAI time use data to fill this critical gap.